Peran Mediasi Kepuasan Nasabah Pada Pengaruh Kualitas Pelayanan Dan Relationship Marketing Terhadap Loyalitas Nasabah Pada Baitul Maal Wat Tamwil (BMT) Maslahah Cabang Wagir Kabupaten Malang - Nashih, Muhammad; Al Idrus, Salim; Prajawati, Maretha Ika (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2024)
The aim of this research is to find out how customer satisfaction mediation impacts service quality and marketing relationships on customer loyalty at BMT Maslahah Wagir Branch, Malang Regency. This study uses quantitative methods. This research involved customers of BMT Maslahah Wagir Branch. Simple random sampling was used to take samples. This research involved 170 people who answered. This data from this research was analyzed using the SmartPLS application with analysis (Partial Least Square). The results of this research show that customer loyalty is directly influenced by the quality of service provided. Unlike relationship marketing which does not directly influence customer loyalty, customer satisfaction influences customer loyalty directly. The mediating role of customer satisfaction shows that service quality and relationship marketing can control the influence of customer satisfaction on customer loyalty